Aktivitas Branding Pada Pelaku UMKM Solo Art Market - Ratna Devi Sakuntalawati; Susantiningrum Susantiningrum; Nur Rahmi Akbarini; Dyah Yuni Kurniawati; Salman Alfarisy Totalia (Jurnal Kewirausahaan dan Bisnis, 2025)
A brand is an essential element for marketing success, but MSMEs need to pay more attention to the quality of their brand. On average, they only pursue profits without paying attention to essential perceptions so that consumers always remember the product brand. Apart from that, implementing the branding strategy could have been more optimal, causing brand loyalty to be shallow. This branding condition is very different if you look at the branding function, which can be used for promotion, attraction, product image and market control. This gap raises questions about branding activities carried out by MSME actors. The research aims to identify branding activities carried out by MSME actors. A quantitative descriptive research method was used to achieve the research objectives, with a sample of all MSME actors taken by the census, totalling 90 respondents. The collection technique uses a questionnaire. The research location is Solo Art Market (SAM). The research results show that most MSMEs in SAM carry out branding activities. The targeted output is the identification of branding activities of SAM MSME actors. This is necessary to maximize sales.Keywords: brand; branding activities; MSMEs; Solo Art Market